Strategies for Targeted Delivery to the Peripheral Nerve - Langert, Kelly A.; Brey, Eric M. (Frontiers in Neuroscience, 2018)
Delivery of compounds to the peripheral nervous system has the potential to be used as a treatment for a broad range of conditions and applications, including neuropathic pain, regional anesthesia, traumatic nerve injury, and inherited and inflammatory neuropathies. However, efficient delivery of therapeutic doses can be difficult to achieve due to peripheral neuroanatomy and the restrictiveness of the blood-nerve barrier. Depending on the underlying integrity of the blood-nerve barrier in the application at hand, several strategies can be employed to navigate the peripheral nerve architecture and facilitate targeted delivery to the peripheral nerve. This review describes different applications where targeted delivery to the peripheral nervous system is desired, the challenges that the blood-nerve barrier poses in each application, and bioengineering strategies that can facilitate delivery in each application.